The Scholarly Travels of Ibn àsakir throughout Iran - Salahedin Monajed; Mohsen Jafari-Mazhab (تاریخ اسلام)
Like many other learned Muslim men, to find knowledge and gather the needed material for his researches, Ibn Asakir, the well-known Muslim scholar, traveled to most of the vast Islamic territories. To learn from different schools of knowledge and various centers of traching in diverse Muslim lands was not only indebted to the lack of modern nation state borders, but also owed much to the endeavor of scholars who regarded the acquisition of knowledge, even to go as far as China and even from the hypocrite and the enemy, as a religious duty. Same as with his other colleagues, Ibn Asakir has given reference to the sources of his acquired knowledge indicating he had taken many lessons from Iranian masters or tutors of Iranian descent.